1990
DOI: 10.1128/jcm.28.3.504-507.1990
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus serotypes 6 and 10 predominate in cattle

Abstract: Calf fecal rotavirus strains were serotyped in enzyme-linked immunosorbent assays, using monoclonal antibodies to the VP7s of serotypes 1, 2, 3, 5, and 6 and to the VP4 of B223 (designated serotype 10). Sixty-six percent of 162 samples were typed as serotype 6, and 7% were serotyped as serotype 10. Most of the untyped strains did not react with a monoclonal antibody directed to a common VP7 epitope, indicating insufficient virus present in the samples. However, seven untyped samples that did react with this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(62 citation statements)
references
References 28 publications
(37 reference statements)
2
55
2
3
Order By: Relevance
“…At least 8 different BRV G-types have been associated with neonatal calf diarrhea (Mebus et al 1971;Woode et al, 1983;Matsuda et al, 1990, Snodgrass et al, 1984, Snodgrass et al, 1990Hussein et al 1993;Parwani et al, 1993). In the United States, type G6 appears to be most widespread, with type G10 accounting for a lower percentage of infections ~ .…”
Section: Introductionmentioning
confidence: 99%
“…At least 8 different BRV G-types have been associated with neonatal calf diarrhea (Mebus et al 1971;Woode et al, 1983;Matsuda et al, 1990, Snodgrass et al, 1984, Snodgrass et al, 1990Hussein et al 1993;Parwani et al, 1993). In the United States, type G6 appears to be most widespread, with type G10 accounting for a lower percentage of infections ~ .…”
Section: Introductionmentioning
confidence: 99%
“…Today rotaviral infections are proven to be a common, economically important cause of calf diarrhea throughout the world. Genotypic analyses of a major neutralization protein VP7 of a bovine rotavirus in diarrheal stools collected in different cattle populations throughout the world have shown that the majority of typeable rotavirus isolates belong to G genotypes 6 and 10 (Alfieri et al, 2004;Chang et al, 1996;Falcone et al, 1999;Garaicoechea et al, 2006;Monini et al, 2008;Parwani et al, 1993;Reidy et al, 2006;Snodgrass et al, 1990). Since the first licensed bovine rotavirus vaccine was a monovalent one, monovalent rotavirus vaccine cannot completely protect against heterologous rotavirus infection (Feng et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys have demonstrated that, so far, G genotype G6 and G10 are the epidemiologically most important bovine rotavirus genotypes worldwide, accounting for 90% of the rotavirus-caused diarrhea approximately. Next to the G6 and G10 genotypes, G8 is the third typical bovine rotavirus genotype (Alfieri et al, 2004;Chang et al, 1996;Falcone et al, 1999;Garaicoechea et al, 2006;Monini et al, 2008;Parwani et al, 1993;Reidy et al, 2006;Snodgrass et al, 1990). In China, our epidemiologic surveillance has shown that rotavirus diarrhea is one of the most important diseases of neonatal calves, and that G6 and G10 were also determined to be the most prevalent genotype of the bovine rotaviruses using nested RT-PCR and sequencing (Chang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Orally administered specific antibodies against enteropathogenic viruses block the development of diarrhea resulting from infections with rota-and coronaviruses (Besser et al, 1988;Snodgrass et al, 1990;Heckert et al, 1999;Erhard et al, 1993;Ikemori et al, 1997).…”
Section: Control Of Intestinal Diseases By Dietary Supplementation Wimentioning
confidence: 99%